Applicability of seed bank assessment methods in wetlands: Advantages and disadvantages - Bao, Francielli [UNESP]; de Assis, Marco Antonio [UNESP]; Pott, Arnildo (Oecologia Australis, 2021)
The soil seed bank is the primary source of regeneration in wetlands and has different assessment methods that vary according to the objective of the study. We evaluated the seed bank composition using three methods: seedlings emergence (EME), seedlings emergence with submersion trays in water (SUB) and screening and counting seeds (COU), and finally, we evaluated the applicability of COU to assess seed predation. The abundance and species richness were evaluated for two years at the end of the flood and dry seasons, in the Brazilian Pantanal. The abundance and species richness differed significantly between methods and seasons. The COU method showed the highest richness (84) and abundance (95.023) followed by EME and SUB. The SUB method reflected only the aquatic community. In the flood season, EME and COU methods showed similar species composition. There were no differences between COU and EME + SUB. The main advantage of COU method was the possibility to assess the seed predation, and we detected that Croton trinitatis had 32% of predated seeds. We consider that wetland ecosystems can be sampled by both methods COU and EME + SUB; however, the complete method that can be used for different purposes is COU, also, must be considered the infrastructure and objective of each study.
Keywords: Diaspore; Floodplain; Predation seeds; Regeneration mechanism; Seedlings